Effect of quality of buffalo oocytes on their maturation rate in vitro - DATTA, T K; GOSWAMI, S L (The Indian Journal of Animal Sciences, 2012)
The present investigation was undertaken to study effect of quality of buffalo oocytes on their maturation rate in vitro, Nearly 70 % of the good quality oocytes reached metaphase-II (M-II) and the corresponding figures for average and poor quality oocytes were 60 and 22 % respectively. A significantly higher percentage of poor quality oocytes was either arrested at M-I or degenerated at the end or culture. The importance of the surrounding cumulus cells of the oocytes for their maturation was confirmed when the good quality oocytes were denuded off their surrounding cumulus cells and allowed to grow in vitro. Only 41 % of such oocytes could reach M-II, However, when these good quality but artificially denuded oocytes were cultured along with extra cumulus cells the maturation percentage increased up to 70 %.